Multi-Therapeutic Potential of Naringenin (4′,5,7-Trihydroxyflavonone): Experimental Evidence and Mechanisms - Azher Arafah; Muneeb U. Rehman; Tahir Maqbool Mir; Adil Farooq Wali; Rayeesa Ali; Wajhul Qamar; Rehan Khan; Ajaz Ahmad; Syed Sameer Aga; Saeed Alqahtani; Nada M. Almatroudi (Plants, 2020)
Extensive research has been carried out during the last few decades, providing a detailed account of thousands of discovered phytochemicals and their biological activities that have the potential to be exploited for a wide variety of medicinal purposes. These phytochemicals, which are pharmacologically important for clinical use, primarily consist of polyphenols, followed by terpenoids and alkaloids. There are numerous published reports indicating the primary role of phytochemicals proven to possess therapeutic potential against several diseases. However, not all phytochemicals possess significant medicinal properties, and only some of them exhibit viable biological effects. Naringenin, a flavanone found in citrus fruits, is known to improve immunity, repair DNA damage, and scavenge free radicals. Despite the very low bioavailability of naringenin, it is known to exhibit various promising biological properties of medicinal importance, including anti-inflammatory and antioxidant activities. This review focuses on the various aspects related to naringenin, particularly its physicochemical, pharmacokinetic, and pharmacodynamic properties. Furthermore, various pharmacological activities of naringenin, such as anticancer, antidiabetic, hepatoprotective, neuroprotective, cardioprotective, nephroprotective, and gastroprotective effects, have been discussed along with their mechanisms of action.